HISTORICAL MEMORY OF THE BYZANTINE EMPRESS THEODORA AS A BASIS FOR INSPIRING REFLECTION IN LITERARY CREATIVE DISCOURSE - Marija Brndevska (Philological Studies, 2023)
This paper comparatively traces the transmission from the chronographic records in the Secret History, left by the Byzantine chronicler of the 6th century, Procopius of Caesarea, to the literary-creative discourse in the instance of writing the novels Theodora and The Purple Robe by the English author Stella Duffy. The goal is to interpret the character of the Byzantine empress Theodora mainly through a gender perspective. Research shows that this empress, through her individualism, clear mind, courage and obvious leadership abilities, managed to ascend from the margins of society to sitting on the throne next to the Byzantine Emperor Justinian I.This is exactly how this Byzantine empress has been preserved in the historical memory, representative and inspiring enough to be reflected in the literary - creative discourse of the author Stella Duffy. In the paper, we will make a detailed observation of the reign of this Byzantine empress, whose character incorporates real leadership attributes, atypical for the period in which she lived, while on the other hand,  we also perceive and analyze the germs of feminist theory in that very same character.